Diagnosis Based on Detection of CXCL10 in Urine as Biomarker for The Determining Diagnosis of Active Lung Tuberculosis - Mertaniasih, Ni Made; Ananda, I Gede Yogi Prema; Soedarsono, Soedarsono; Kusumaningrum, Deby (Indonesian Journal of Tropical and Infectious Disease, 2021)
Tuberculosis diagnosis is an important component in decreasing TB incidence and prevalence. Because of the difficulty to collect sputum in some cases, urine specimens are used as it is easier to garner. One of the biomarkers in urine that can be used to diagnose pulmonary TB is IP-10, which can be represented by the CXCL10 gene. The study aims to determine the accuracy of diagnosis based on detection of the CXCL10 gene in urine as a biomarker for the patients with suspected pulmonary TB in Dr. Soetomo Hospital in Surabaya from November 2019 until March 2020. Thus, this is an observative laboratory research with a cross-sectional study. CXCL10 gene was examined using PCR for 36 urine samples, and then, the data, together with the medical records of clinical manifestations of pulmonary TB, GeneXpert MTB /RIF, blood count, and thorax radiograph, were processed using IBM SPSS Statistics 26. The results of the GeneXpert MTB/RIF and thorax radiograph criteria show positive results of pulmonary TB, which were 44.4% and 69.4% respectively. CXCL10 gene was not found in all urine of healthy people (negative), while 2.8% (1/36 samples) positive CXCL10 gene was found in a patient with positive GeneXpert, also with negative clinical manifestations and urine culture. In this study, the accuracy of diagnosis based on detection of the CXCL10 gene in urine for diagnosis of active pulmonary TB was 2.8%. Future research is needed to improve the methods, among them are bigger size of urine samples and clearer medical history of patients.